Potential Antioxidant Activity of the Unused Part of Tamarillo (Solanum betaceum Cav.) - Atina Rizkiya Choirunnisa; Zhafira Amalia Regiana; Muhamad Insanu; Rika Hartati; Hegar Pramastya; Defri Rizaldy; Irda Fidrianny (Jurnal Kimia Sains dan Aplikasi, 2025)
Tamarillo (Solanum betaceum Cav.) is a member of the Solanaceae family that contains phenolic and flavonoid compounds. The fruit of the tamarillo is commonly consumed. However, other parts that are rarely used also have many potential benefits, including antioxidant activity. This study aims to evaluate antioxidant activity of used part (flesh) and unused part (leaves and peel) extracts of tamarillo through ascorbic acid equivalent antioxidant capacity (AEAC), phenolic and flavonoids content, correlation the phenolic and flavonoid content on antioxidant activity, correlation the DPPH and CUPRAC methods and the levels of flavonoid compound in selected extract. Three organs (flesh, leaves, peel) were extracted using polarity solvents (n-hexane, ethyl acetate, ethanol). Antioxidant activity was conducted using DPPH and CUPRAC assays, and total phenolic acid and flavonoid acid were also investigated. The result showed that the highest antioxidant activity of tamarillo extracts using DPPH and CUPRAC methods was given by ethanol leaves, 94.917 ± 3.920 and 110.182 ± 7.987 mg AEAC/g sample. The highest TPC in the ethanol leaves extract 10.416 g GAE/100 g, while the highest TFC in the n-hexane leaves extract 8.367 g QE/100 g. Phenolic and flavonoid compounds were identified as significant contributors to the antioxidant activity, with both assessment methods showing a strong linear correlation. In conclusion, Tamarillo leaves had the potential to be a natural antioxidant source, with a rutin content of 0.088%, according to HPLC analysis.